Mechanism Design for Robotics Proceedings of the 4th IFToMM Symposium on Mechanism Design for Robotics - Gasparetto, Alessandro; Ceccarelli, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume contains the Proceedings of the 4th IFToMM Symposium on Mechanism Design for Robotics, held in Udine, Italy, 11-13 September, 2018. It includes recent advances in the design of mechanisms and their robotic applications. It treats, among others, the following topics: mechanism design, mechanics of robots, parallel manipulators, actuators and their control, linkage and industrial manipulators, innovative mechanisms/robots and their applications. This book can be used by students, researchers and engineers in the relevant areas of mechanisms, machines and robotics. .
Provisional table of contents:Linkages and Manipulators -- Innovative Mechanisms/Robots and Their Applications -- Actuators and Control -- Mechanism Design -- Mechanics of Robots -- Parallel Manipulators.
Keywords: Control engineering; Robotics; Automation; Machinery; Control, Robotics, Automation; Control and Systems Theory; Machinery and Machine Elements